ANALYSIS OF SMK3 IMPLEMENTATION AND CAUSES OF WORK ACCIDENTS AT PT. BUMI DUTA PERSADA (BDP) IN TANGERANG REGENCY - Samsidik Samsidik; Naufal Affandi; Ade Manggala H (Jurnal Ekonomi, 2023)
This study was conducted with the aim of analyzing the implementation of SMK3 and the causes of work accidents at PT. Bumi Duta Persada (BDP) in Tangerang regency when carrying out work there are many risks that can occur, namely work accidents are very risky to occur, Factors causing work accidents can occur due to 2 conditions, namely unsafe project locations or unsafe labor behavior, unsafe labor behavior has a higher influence than unsafe project locations, Unsafe worker behavior occurs due to several things, namely lack of awareness of wearing Personal Protective Equipment (PPE), joking with friends while working, procedural errors and not using assistive equipment while working, work accidents are due to the low implementation of Occupational Safety and Health (K3). To minimize the level of risk of work accidents, it is necessary to implement an Occupational Safety and Health Management System (SMK3). One of the causes of the increasing number of work accidents is the absence of optimization of supervision and implementation of K3 and K3 behavior in the workplace. This research method is qualitative descriptive research Data analysis is by Preliminary Hazard Analysis (PHA) method and 5W – 1H method. Bumi Duta Persada (BDP) in Tangerang regency. The results of the study were the lack of use of Personal Protective Equipment (PPE) when doing work, causing small category accidents and medium category accidents. there were accidents during concrete casting work and road paving work with a total number of accidents, 16 accidents with a small accident category, 13 accidents and 3 accidents in the medium category, lack of awareness from workers in complying with regulations set by the company such as working in accordance with standard operating procedures (SOP) and using PPE while working, factors causing non-fulfillment of the implementation of the health management system and work safety (SMK3), namely the lack of awareness of workers about work safety and also the limited budget of funds in the implementation of SMK3, the level of work risk is included in the small risk level of the value range (1 - 4) where the level of danger is small with a small hazard classification, this happens because the level of work falls into the category of small level risk.